Reação metabólica à infecção no hospedeiro. - Pereira, Paulo Câmara Marques [UNESP]; Burini, Roberto Carlos [UNESP] (My University, 1992)
At the site of local reaction to infection the interleukin-1 (1L-1) is released signaling to distant tissues the presence of infection and attempting to strengthen the host's defenses and inhibit the bacterial growth. This phenomenon is accompanied by anorexia and fever. The muscle-protein breakdown is sustained and the released amino acids are taken up by the liver and other RE structures where they are used as substrates for energy and for synthesis of defense-related proteins. The metabolic adaptations to sepsis include hyperthermia, increased synthesis of hepatic globulins, development of granulopoiesis and neutrophilia and redistribution of serum iron and trace minerals.
Host metabolic reaction to infection
Keywords: protein; anorexia; bacterial infection; energy metabolism; fever; immunology; metabolism; pathophysiology; Anorexia; Bacterial Infections; Energy Metabolism; English Abstract; Fever; Proteins